Preliminary study of sea water intrusion using geographic information system in Temon, Kulon Progo, Yogyakarta, Indonesia - Eva Putriany; Sadewa Purba Sejati (Universitas Negeri Malang, 2023)
Temon Sub Districts is an administrative area of Kulon Progo Regency, which borders the South Sea (Indian Ocean). The Temon Sub District is directly adjacent to the waters, so it potentially experiences intrusion like other coastal areas in Indonesia. Therefore, groundwater conditions related to the phenomenon of water intrusion need to be identified. The purpose of this study was to estimate seawater intrusion using a geographic information system (GIS) and water quality variables in the Temon Subs Districts. In this study, we used data on electrical conductivity (EC), total dissolved solids (TDS), and groundwater salinity. The sampling was carried out using a systematic random sampling method. Meanwhile, the data analysis was carried out in a qualitative descriptive manner using the spatial interpolation feature in the Arc GIS 10.8 software. Based on the research results, it is suspected that seawater intrusion has occurred in several locations in Temon Sub Districts. The highest suspected seawater intrusion was found in the vicinity of Jangkaran Village, Kalidengen Village, and Plumbon Village. The EC, TDS, and salinity values suggested that around 26% or 9.68 km2 of the area has intruded. This research is expected to enrich references regarding the mapping of seawater intrusion in coastal areas.